P01.118 Prognostic factors and management of gliomatosi cerebri (GC) from real life experience of two neuroncology centers. (19th September 2018) - Lombardi, G; Bellu, L; Sabatino, G; Caccese, M; Berti, F; Busato, F; Della Puppa, A; D'Avella, D; Olivi, A; Zagonel, V
Abstract: Background: GC is defined as a rare pattern of growth of gliomas, involving three or more cerebral lobes. Considering its rarity, it's still difficult to define prognostic factors and standard of treatment. Retrospectively, we analyzed patients (PT) with GC from two neuro-oncology centers to identify main prognostic factors and the optimal management. Material and Methods: Medical records of patients ≥ 18years, with histological and/or radiological diagnosis of GC occurred between 2006 and 2017 were reviewed. Median progression free survival (PFS) and overall survival (OS) were calculated by Kaplan-Meier method. Results: We analyzed 33PT, 22males and 11female; ECOG performance status (PS) was 0–1 in 21PT and ≥ 2 in 12PT. 22PT underwent biopsy: 16 were astrocytomas, 6oligodendrogliomas. MGMT was detected in 14PT: it was metilated in 8cases. IDH1 was analyzed in 16PT: it was mutated in 10PT. 15 of 33PT showed localized enhancing lesions at diagnosis. 9PT(27%) were treated with radiation therapy (RT) plus concurrent temozolomide (TMZ), 22PT(67%) received only TMZ, and 2PT(6%) underwent RT alone. Best response was complete response (CR) in 3PT(3%), partial response (PR) in 9PT(27%) and stable desease (SD) for 15PT(45%); only 8PT(25%) had a progression desease (PD). For all PT, PFS and OS were 19.1 and 30.7 months (ms) respectively. For PS 0–1 and ≥2, PFS was 34.6 vs 3.4ms (p<0.0001) and OS was 42 vs 8.9ms (p<0.0001) respectively. Metilated MGMT was associated with longer PFS (41.6 vs 8.9ms, p=0.05) and OS (52.7 vs 14.6ms, p=0.009); for IDH1 mutated and IDH wt, PFS was 52.7 vs 8.9ms (p=0.006) and OS was 57.7 vs 41ms (p=0.02) respectively. No significantly difference was detected about treatments: PFS was 11.1 vs 19.1ms and OS was 40.4 vs 41.7ms for RT+TMZ and TMZ/RT alone, respectively. No significantly difference was found beetween enhancing and non-enhancing lesions: PFS was 11.1 vs 23.1ms (p=0.2), OS was 14.6 vs 41.7ms (p=0.1). Regarding histological subtype, OS was 42.0 vs 52.7ms and PFS was 41.6 vs 28.6ms for astrocytoma vs oligodendroglioma respectively. PT having PR or CR reported a longer OS versus PT with SD and PD as best response: 4.0ms for PD, 30.7ms for SD and 38.5ms for PR+CR (p<0.0001). 13 of 22PT underwent second-line treatment after relapsing: 1PT did RT+TMZ, 10PT chemotherapy alone (fotemustina, PCV/PC, TMZ), and 2PT RT alone; PTS receiving a second-line treatment had a longer OS: 30.7 vs 6.5ms (p=0.04). Conclusion: PS, MGMT and IDH1 seems to have an important prognostic significance, whereas, type of treatment doesn't seem to affect survival. Best response could be a good surrogate of OS.